Assessing the stability of uncentrifuged serum and plasma analytes at various post-collection intervals - Mokhsin Atiqah; Subramaniam Poonaresi; Sivaneson Sivasooriar; Nheu Nelson; Ramaloo Gobhy; Hanifah Azana S.; Mahathevan Sumitha B.; Nadarajah Mohanaraja; Sampasivam Gayathiri; Mohd Ismail Aletza; Abdul Rahman Thuhairah (Journal of Laboratory Medicine)
Our study aimed to assess the stability of 26 biochemistry analytes in serum or plasma samples separated from blood samples centrifuged at different time intervals after collection, simulating sample transport via despatch delivery systems.